Route of delivery to the airway influences the distribution of pulmonary disease but not the outcome of Mycobacterium tuberculosis infection in rhesus macaques. (January 2016) - Sibley, Laura; Dennis, Mike; Sarfas, Charlotte; White, Andrew; Clark, Simon; Gleeson, Fergus; McIntyre, Anthony; Rayner, Emma; Pearson, Geoffrey; Williams, Ann; Marsh, Philip; Sharpe, Sally
Summary: Non-human primates (NHP) provide a key component in the preclinical assessment pathway for new TB vaccines. In the established models, Mycobacterium tuberculosis challenge is typically delivered to airways of macaques either by aerosol or bronchoscopic instillation and therefore, an understanding of these delivery routes would facilitate the comparison of data generated from models using different challenge methods. This study compared the clinical effects, antigen-specific IFNγ response profiles and disease burden following delivery of comparable doses of M. tuberculosis to the lungs of rhesus macaques by either aerosol or bronchoscopic instillation. The outcome of infection in terms of clinical effects and overall disease burden was comparable between both routes of challenge. However, the pathology in the lungs differed as disease was localised to the site of inoculation following bronchoscopic instillation while aerosol exposure resulted in lesions being evenly distributed through the lung. Whilst the IFNγ response to PPD was similar, responses to CFP10 and ESAT6 peptide pools measured with an ex vivo ELISPOT differed with regards to responses to the N-terminal regions depending on the route of infection. Both challenge routes therefore provide valid and comparable models for evaluation of new TB vaccines, although subtle differences in host responses may occur.